Haliclona (Reniera) portroyalensis n. sp., a new chalinid sponge (Porifera, Demospongiae, Haplosclerida) from the southeast coast of Jamaica - Jackson, Celia P.j.; de Weerdt, Wallie H.; Webber, Mona K. (Zootaxa, 2006)
A new demosponge species of the order Haplosclerida, growing on mangrove roots in Port Royal, southeast coast Jamaica, is described as Haliclona (Reniera) portroyalensis n. sp. A short overview of previous work on Chalinidae and on Jamaican sponges is given, and we discuss how the new species differs from other member of the genus and subgenus. The holotype is purple alive and beige when preserved in alcohol. It has digitate and bulbous processes with scattered oscula, some laterally plush, and measuring 2–3 mm with larger ones up to 6 mm on the bulbous areas. The consistency is soft, and it is easily torn, but resilient. The megascleres, oxeas are straight to slightly curved with short conical points. The only microscleres are toxas which are of varying lengths numerous and distributed throughout the ectosome and choanosome.